The Effect of Problem Based Learning Model on Students Mathematic Representation Ability and Student Adversity Quotient at SD Islam Setia Nurul Azmi Medan - Siti Fadillah; Kms. Muhammad Amin Fauzi; Anita Yus (BIRCU, 2020)
This study aims to determine: (1) how much influence the problem-based learning model has on students' mathematical representation abilities, (2) how much influence is the problem based learning model on students' adversity quotient, 3) whether there is an interaction between the learning model and KAM on students' representation abilities, (4) whether there is an interaction between the learning model and KAM on students' adversity quotient, and (5) how to analyze students' mathematical representation abilities seen from the indicators. This research is about quasi-experimental research. The population of this study was all fourth grade students of SD Islam Setia Nurul Azmi Medan in the academic year 2020/2021 which consisted of four classes. Samples were selected by random sample of two classes. The instruments used were the representation ability test and the attitude scale adversity quotient. The data obtained was then analyzed using ANACOVA and ANAVA in the SPSS 20 program. The results showed: 1) the magnitude influence of the PBL model on the mathematical representation ability of 0.931 or 93.1%, 2) the magnitude influence of the PBL model on the adversity quotient is 0.967 or 96.7%, 3) there is an interaction between the initial ability and PBL learning to the mathematical representation ability of students with an Fcount of 3.906 so that Ha is accepted and H0 is rejected, 4) there is no interaction between the initial ability and learning PBL to the adversity quotient for students with an Fcount of 0.198 so that H0 is accepted, 5) the ability of the student's visual representation indicator is high with an average score in the experimental class 76 and the control class 72, the ability of the student's visual representation indicator is high with an average score in the experimental class 72 and the control class 68, The indicator ability of the students' representation of words or written text was moderate with the average score in the experimental class 65 and the control class 61.